Verified Approximation Algorithms - Eßmann, Robin; Nipkow, Tobias; Robillard, Simon; Sulejmani, Ujkan (Logical methods in computer science, 2022)
We present the first formal verification of approximation algorithms for NP-complete optimization problems: vertex cover, independent set, set cover, center selection, load balancing, and bin packing. We uncover incompletenesses in existing proofs and improve the approximation ratio in one case. All proofs are uniformly invariant based.